“FARABI…. ? - Abdurakhmanova Manzura Batirovna; Otajonov Jahongir (American Journals, 2023)
The need in the process of education to use the phenomena of nature and in this way to educate a person who knows how to treat other people correctly, learn the rules of the internal structure of society and meet its requirements.
Keywords: Farabi, mind, behavior, Central Asia, Baghdad science